Numerical Study of the Flow of Pollutants during Air Purification, Taking into Account the Use of Eco-Friendly Material for the Filter—Mycelium - Vaidotas Vaišis; Aleksandras Chlebnikovas; Raimondas Jasevičius (Applied Sciences, 2023)
To improve air quality, it is customary to apply technological measures to isolate or retain pollutants by influencing the polluted stream in various ways to effectively remove the pollutants. One of the most commonly used measures is a filter, in which the air flow passes through a porous aggregate. A variety of filter materials allows very selective and precise cleaning of the air flow in non-standard or even aggressive microclimate conditions. In this paper, the environmental aspect of the used materials is discussed, and a theoretical model of an adapted mycelium is proposed as an alternative to the use of filter materials to predict air flow purification. In the created numerical model of an idealized filter, several cases are considered when the pore size of the mycelial fillers reaches 1.0, 0.5 and 0.1 mm, and the feed flow velocity reaches 1–5 m/s. Moreover, in the mycelium itself, the flow velocity can decrease and approach the wall to a value of 0.3 m/s, which is estimated for additional numerical studies of interaction with the surface. These preliminary studies are aimed at establishing indicative theoretical parameters for favorable air flow movement in the structure of the mycelium.